EFFECTS OF IRRIGATED AGRICULTURE ON THE GROUNDWATER REGIME IN THE FOOTHILLS - Sadullaev, Azamat Nafiddinovich (Educational Research in Universal Sciences, 2022)
In the countries of Central Asia, including the Republic of Uzbekistan, flat areas suitable for irrigation in large river valleys have been exhausted. The development of irrigated agriculture towards the sub-mountain plains, that is, the irrigation of uneven and hypsometrically high areas, causes a number of environmental problems. These problems include soil erosion, soil salinization, changes in the quality and regime of groundwater, increased migration of salts in the soil and subsoil to the lowlands, and others. The Ulus desert is located in the middle course of the Zarafshan river on the plain on the northern slopes of the Karatepa and Zirabulok mountains.